The Influence of Management Accounting Information Systems on Financial Statements Performance in Retail Sector in Serang Regency - Wildan Nuryanto, Uli; Sutisna, Nining Sulastri; Kusuma, Bayyu Indra; Sari, Gema Ika; Khaeruman; Komarudin, Mamay; Suadma, Udin (Yayasan Ilomata, 2025)
This study aims to analyses the effect of management accounting information system (MAIS) on financial statements performance of retail sector in Serang Regency. A quantitative approach was used with the linear regression analysis method. The sampling method was carried out using purposive sampling of 60 respondents who were finance managers, accounting staff and operational managers who used MAIS. The results showed that MAIS had a significant effect on the performance of financial statements with a statistical t value of 15.388. And the magnitude of the regression constant is 11.802 and the path coefficient value is 0.444 which indicates that each one unit increase in MAIS implementation will increase the performance of financial statements by 0.444, the magnitude of the R2 value of 0.701 indicates that 70.1% of the financial statement performance variable can be explained by the MAIS variable while the rest is influenced by other variables. The results of this study reinforce previous findings that the implementation of an effective MAIS will make a major contribution in improving the effectiveness, efficiency, and accuracy and timeliness of financial reports. The implications of the results of this study encourage retail companies to continue to improve the management of their accounting information systems to support better and optimal managerial decision making.